Numerical modeling of the performance of active and passive bolts installed at an Illinois basin coal mine - Ray, A.; Gadde, M.; Spearing, Sam (2013)
Numerical modeling based approaches have been used in past to understand the performance of different roof bolt systems under varying geo-mining conditions to be used as primary supports in underground coal mines. However, modeling exercises coupled with field instrumentation data are few and far between. Considering the popularity and versatility of numerical modeling, an attempt is made in this paper to see if it is possible to explain the trends in bolt loads as observed by some in-situ studies. Specifically, this paper describes the in-situ monitoring of roof bolt behavior at an Illinois Basin coal mine and then discusses the results from a numerical modeling exercise conducted to explain the observed bolt performance. Copyright 2013 ARMA, American Rock Mechanics Association.